2022
DOI: 10.1108/jfbm-07-2022-0090
|View full text |Cite
|
Sign up to set email alerts
|

Related party transactions and earnings management in family firms: the moderating role of board characteristics

Abstract: PurposeThe purpose of this paper is to investigate the effect of family control on the association between related party transactions (RPTs) and different forms of accrual-based earnings management (AEM) and real earnings management (REM), analyzing the effect of board characteristics on the possible association.Design/methodology/approachThis paper studies a sample of Italian non-financial listed firms over the 2014–2019 period, by GLS regression models, controlling for the fixed effects of the company's sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 121 publications
1
22
0
1
Order By: Relevance
“…Our study contributes to the corporate governance literature by investigating the effect of CEOs' characteristics on earnings management to meet or beat earnings thresholds during an economic crisis period. It also contributes to the growing stream of research on family firm governance (Gavana et al, 2022) by providing evidence of the moderating effects of family ownership on the CEO attributes-earnings management relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Our study contributes to the corporate governance literature by investigating the effect of CEOs' characteristics on earnings management to meet or beat earnings thresholds during an economic crisis period. It also contributes to the growing stream of research on family firm governance (Gavana et al, 2022) by providing evidence of the moderating effects of family ownership on the CEO attributes-earnings management relationship.…”
Section: Discussionmentioning
confidence: 99%
“…The larger the value of kEMk, the more it will be interpreted as evidence of EM. In this research study, various control variables have been used in line with related previous studies (Beuselinck and Deloof, 2014;Gavana et al, 2022;Khan and Kamal, 2022;Kim and Yi, 2006;Muttakin et al, 2017;Seifzadeh et al, 2022). This research study used some control variables that may affect the value of EM as well as the FBG affiliation dummy, such as firm size, profitability, leverage, a loss dummy, firm growth, firm age and the BIG4 audit firms.…”
Section: Population Sample Size and Data Collection Of The Studymentioning
confidence: 99%
“…In a recent paper by Gavana et al (2022), it is found that related party transactions in family businesses might be used as a substitute/complement for earnings manipulation, especially when family control is strong, in line with the principal-principal conflict. Jiang and Peng (2011) state that the severity of agency conflicts in a family business depends on the institutional setting in which it operates.…”
Section: Directorates and Family Firm Performancementioning
confidence: 99%
“…This situation is worse in settings of high ownership concentration and poor external corporate governance like Mexico, where legal frameworks and market controls are incipient (Lien et al, 2016). Interlocks can increase the influence of the involved parties (business families), making it possible for them to jointly benefit from expropriating other stakeholders, and reducing companies' outcomes (for example, by relocating assets to private (family) hands -Drago et al, 2015; or by stimulating related party transactions, which might have a similar effect to managing earnings downwards to reduce dividend payments - Gavana et al, 2022). Accordingly, the following hypotheses are proposed:…”
Section: Directorates and Family Firm Performancementioning
confidence: 99%
See 1 more Smart Citation